Human chromosome 22. Issue 2 (February 1987) - Kaplan, J C; Aurias, A; Julier, C; Prieur, M; Szajnert, M F
Abstract : The acrocentric chromosome 22, one of the shortest human chromosomes, carries about 52 000 kb of DNA. The short arm is made up essentially of heterochromatin and, as in other acrocentric chromosomes, it contains ribosomal RNA genes. Ten identified genes have been assigned to the long arm, of which four have already been cloned and documented (the cluster of lambda immunoglobulin genes, myoglobin, the proto-oncogene c-sis, bcr). In addition, about 10 anonymous DNA segments have been cloned from chromosome 22 specific DNA libraries. About a dozen diseases, including at least four different malignancies, are related to an inherited or acquired pathology of chromosome 22. They have been characterised at the phenotypic or chromosome level or both. In chronic myelogenous leukaemia, with the Ph1 chromosome, and Burkitt's lymphoma, with the t(8;22) variant translocation, the molecular pathology is being studied at the DNA level, bridging for the first time the gap between cytogenetics and molecular genetics.